King Zog’s Foreign Policy with Neighboring Countries - Yzeiraj, Emirjola (Mediterranean Journal of Social Sciences, 2021)
Zogu has resolutely defended the freedom and independence of his country. Zogu consolidated diplomatic relations with neighboring countries and the political strategy followed by him brought not only economic stability, but also protection of the territory. Seen from that prespective, the purpose of this paper is to show that the policy pursued by King Zog, influenced the establishment of peace in the country and protected the entire Balkans by not further complicating the situation and neutralizing the greedy interests and intentions of Yugoslavia for the territory of Albania, especially St. Naum. In 1924 King Zog had also a possed Yugoslavia’s intervention and intrigues. Throughout his policy, he aimed to achieve Balkan’s peace, because Zogu understanding very well that this would bring peace to Albania as well.  The foreign policy led by Zog, deprived neighboring countries of any wishing conflicts. Thus the peace in Europe would have been in jeopardy as a result of threatening Balkans’s peace.   Received: 7 July 2021 / Accepted: 30 August 2021 / Published: 5 September 2021